International experience of a direct supervisor-does it matter for self-initiated expatriates' adjustment? - Irma Baneviciene; Luisa Helena Pinto; Vilmante Kumpikaite-Valiuniene (PLoS ONE)
Due to increasing global mobility flows, self-initiated expatriates (SIEs) in both employee and managerial roles are now commonplace. However, the influence of direct supervisors' international experience on the adjustment of SIEs remains underexplored. This study, grounded in signaling and similarity-attraction theories, addresses this gap through a qualitative examination of supervisors with international experience and at least one SIE under their supervision. The findings indicate that both foreign-born and locally born supervisors perceive their international experience as valuable in managing their international teams. Foreign-born supervisors, more frequently than their locally born counterparts, interpreted the uncertainty signals from their SIE employees as a reflection of empathy and open-mindedness, attributes shaped by their international backgrounds and cultural insights. Furthermore, the results suggest that all direct supervisors focus their support and actions primarily on facilitating SIEs' adjustment in the work environment, rather than in the non-work environment. This research offers theoretical and practical insights for international human resource management, highlighting the positive impact of supervisors with international experience on the onboarding and adjustment processes of new SIEs, thereby enhancing the management of international teams.